T.H.M. Repertuarındaki İstanbul Türkülerinin İncelenmesi - Bakar, Celal (Sosyal Bilimler Enstitüsü, 1998)
Türk Halk Müziği repertuarındaki İstanbul türkülerinin incelenmesi konulu bu çalışma dört bölümden oluşmaktadır. Birinci bölümde (giriş), konunun seçilme nedeni, yapılan çalışmanın amacı, kullanılan yöntemler; İkinci bölümde İstanbul ilinin tarihçesi, coğrafi konumu, iklim ve nüfus bilgileri; Üçüncü bölümde tarihsel süreç içinde İstanbul’un kültürel yapısı ve öğerleri; Dördüncü bölümde THM repertuarındaki İstanbul türkülerinin müzikal analizi; Sonuçlar ve öneriler bölümünde konunun küçük bir özeti ile çözüm önerileri; verilmiştir.

In this thesis, we have tried to study twenty four folk melodies which belong to İstanbul in every aspect. In this study, we have examined in detail the history of İstanbul, its past civilizations, geography, beliefs and moral structure, religional structure, marriage traditions, traditions of birth and child, traditions of death, traditional hand art, proveıbs, idioms, folk dans, folk literatüre, and folk music. The reason for this is that we believe that the afForementioned, are the factors that influence music deeply. We thought that without examining them, we cannot analyze İstanbul folk music thoroughly. Therefore we have also examined them extremely careful. The main reason in choosing to examine the folk music of İstanbul is that there have not been a thorough and detailed study in this area. Our procedure in this study will be as such: a) Parts b) Sentences, that form a whole with small questions and qnswers c) Small music sentences.Expressions that form the sentences in (b). In our thesis, we will use big letters as A,B,C symbolically to denote parts, and small letters as a,b,c to denote sentences. The first settlement in İstanbul, where it was determined by the environmental excavations that the history of settlement goes up to the Paleolithic Era, has been built in B.C. 680. The Megarians who escaped from Dorians that invaded Greece by colonization have come to Bosporus and have built Kalkedon (Kadıköy) .The secong group of Megarians in the leadership of Byzas have settled to the opposite side of Kalkedon following the suggestion of Delfi Kahi in B.C. 666, and named the new town as Byzantion. Byzantion has been invaded by Persians in B.C. 513 and by Spartans in B.C. 405. Later on, in B.C. 318, it was invaded by Bitins during the Sea Tribe Migration of Antigonos who was one of the commanders of Alexander The Great. It was made the Capital by Constantine in 11 May 330. After this date, the town was named as Constantinople. İstanbul became the most important culture and art çenter of Christianity during the whole Middle Age after Constantine aceepted Christianity. Various attacks have been made against the town by Sasans in 605, by Islav-Avars in 626, by Arabians in 717, by Russians in 863, and by Bulgarians in 924. But none of these attacks succeeded. The Ottoman Emperor Yıldınm Beyazıt surrounded the town twice; the first was in 1391, and the second was in 1397. In 1422, n.Murat surrounded it again. But this was unsuccessfiıl too. Finally, in 1453, Fatih Sultan Mehmet invaded the town and it became a part of the Ottoman Empire. İstanbul became the capital. In a short time, İstanbul became one of the most important culture and art centers of Islamic world. İstanbul was under the military occupation of Entente Powers in 1918, and the occupation was över in 6 October 1923. İstanbul owns a rich folklore in every stage of its historical development. Ali of these stages formed a very rich accumulation due to its cosmopolitan structure and strategic location. In the folklore of İstanbul, the Byzantine and Ottomoan elements, cultural elements of etnical groups living in the town, and elements of migrations from various regions are ali side by side. İstanbul is built on the two sides of Bosporus which separates the continents Asia and Europa, and its area is 5.712 km2. The land of the city covers the East Marmara part of the Marmara Region. It resides betvveen the 28° 01 and 29° 55 east longitudes, and between the 41° 33 ve 40° 28 north latitudes. İstanbul is sorrounded with Kocaeli from the east and south-east, with Bursa from the south, with Tekirdağ from the west, and with Kırklareli from the north-west.We have determined 24 collected melodies belonging to the Turkish folk music that owns an important place within the folklore of İstanbul. The melodies are studied with respect to their altered notes, cadances, forte notes, sound length, methods, and measures; then the notes are analyzed with respect to their forms and the results are stated in the form of group expressions and symbolic expansions. İn our investigation; the smallest passages that have a thematic unit are investigated as small sentences, passages fromed of at least two or more small sentences are investigated as sentences, and the whole made up of small sentences and sentences are investigated as parts. The parts are designated with capital letters like A,B,C; the sentences with symbols like x,y,z,Q,a,|3,5; and the small sentences with letters like a,b,c. The instrumental portion is shown with the letter S, and the song portion is shown with the letter Ş. Some results that we have determined after the investigation of twenty four melodies are the following: In these melodies, the effects of Classical Turkish Music which is widespread throughout the city are seen. The reason of this is the living of Literary School and Folk Literatüre, Classical Turkish Music and Folk Music together. The reason that the 9-timed ones are used intensively arises from the effect of the Rumelia melodies in İstanbul.The long musical sentences are not used in İstanbul melodies. In these melodies, the tune structure is respected. The reason of this is obvious that it arises from the effects of Classical Turkish Music. We have seen that the investigated melodies have differences in terms of the motion. We see ali types of the motions vvhich are named as going-dovvn, rising-up, and going-down-rising-up.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1998
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1998
Keywords: Müzik; Ezg; Kültürel yapı; Türk halk müziği; Türküler; İstanbul; Melody; Cultural structure; Turkish folk music; Folk songs; Istanbul